2014
DOI: 10.4332/kjhpa.2014.24.1.13
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Supplier Induced Demand on Increase in Medical Aid Expenditure

Abstract: Background: A need arises to efficiently control health expenditure for medical aid due to a sharp increase in medical aid expenditure. This study experimently analyzes the impact of physician behavior on medical use for medical aid beneficiaries using supplier induced demand (SID) theory. Methods: This study looks into analyze SID effect using expenditure factor analysis of medical aid for the years between 2003 and 2010 in comparison with health insurance. Moreover, this study analyzes the existence and scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Total medical expenses also increased, with growth rates similar to that of health insurance expenses, from 4.2 trillion won to 6 trillion won during the same period [3]. However, health care service use and number of hospitalization days in medical aid beneficiaries were about four times higher than that in health insurance subscribers, and the medical expenses per person in medical aid beneficiaries were about 3.6 times higher than that in health insurance subscribers [4]. It has been argued that medical aid beneficiaries' overuse of free medical services has been deemed one of the main causes for the rise in medical costs.…”
Section: Introductionmentioning
confidence: 99%
“…Total medical expenses also increased, with growth rates similar to that of health insurance expenses, from 4.2 trillion won to 6 trillion won during the same period [3]. However, health care service use and number of hospitalization days in medical aid beneficiaries were about four times higher than that in health insurance subscribers, and the medical expenses per person in medical aid beneficiaries were about 3.6 times higher than that in health insurance subscribers [4]. It has been argued that medical aid beneficiaries' overuse of free medical services has been deemed one of the main causes for the rise in medical costs.…”
Section: Introductionmentioning
confidence: 99%
“…If this inefficient use is not dealt with effectively, it may result in a serious waste of resources. Previous studies [54,55] have shown that, when medical insurance coverage is universal, there is a moral hazardmedical service providers may over-provide medical services, and patients may overuse medical services. For example, expensive tests such as transthoracic echocardiography [56] and various imaging examinations [57][58][59] are performed in patients with low probability of pre-examination.…”
Section: Discussionmentioning
confidence: 99%